Ireland : Financial Sector Assessment Program-Technical Note on Insolvency and Creditor Rights. (IMF Staff Country Reports; Country Report, 2022)
This note analyzes select aspects of the system for insolvency and creditors' rights in the context of an overall assessment of the Irish financial sector. It focuses on two areas: (i) the use and effectiveness of the corporate restructuring regime (examinership) and (ii) the resolution of mortgage related NPLs. Corporate restructuring was considered particularly relevant given that the authorities are currently in the process of amending their insolvency system to incorporate the provisions of the European Directive on Preventive Restructuring Procedures (the "EU Directive") and have recently adopted a new debt resolution regime for small and micro-sized enterprises. The mission team also focused on the resolution of mortgage related NPLs, given that they constitute 46 percent of all NPLs (total loans) in the retail banking system and pose a challenge to the effectiveness of the overall system for debt resolution and creditors' rights. This analysis has been conducted against the international insolvency standard (the "Standard"), where relevant 2.